Vulnerabilities of BOT Scheme and Ways to Overcome Them Under PPP: Cross-Country Comparison of PPP Systems Among Selected Countries. (July 2019) - Tsukada, Shunso
Many developing countries have resorted to BOT (build–operate–transfer) scheme for infrastructure development. Although BOT scheme would bring significant benefits to developing countries, it conceals structural vulnerabilities. This has made the private sector hesitant in investing in BOT projects unless key risks are covered by governments under public private partnership (PPP) arrangements. Having seen this problem, developing countries have offered overly lucrative guarantees to private investors, which have ended up with huge payments at a later stage. The purpose of this study is to find a kind of PPP measures which would be effective in getting the private sector to participate in BOT projects with little public-sector support being offered. For this purpose, a cross-country comparison was conducted, which has identified that some of PPP measures adopted in India are effective. Although their applicability to other developing countries is limited, it was found possible if combined with appropriate measures and confined to right sectors.